Antioxidant Activity of Weeping Fig (Ficus benjamina L.) Leaf Extract: A Comparative Analysis Using ABTS and FRAP Assays - Wicahyo, Septian Maulid; Raharjo, Danang; Permata, Bangkit Riska (LPPM Universitas Duta Bangsa Surakarta, 2025)
Ficus benjamina L. (weeping fig) has been traditionally used in folk medicine, but its antioxidant potential remains scientifically underexplored. This study aimed to comprehensively evaluate the in vitro antioxidant activity of a 70% ethanolic extract of F. benjamina leaves using two assays. The extract was prepared by maceration and subjected to phytochemical screening. Antioxidant activity was assessed through the ABTS radical scavenging assay, reported as IC?? and Trolox equivalents (TE), and the FRAP reducing power assay, reported as FeSO? equivalents (FE). Phytochemical analysis revealed abundant flavonoids, phenolics, and tannins. The extract demonstrated potent antioxidant activity, with an IC?? of 28.4 ?g/mL in the ABTS assay and a value of 412.3 mg TE/g. The FRAP assay confirmed strong reducing power, with a value of 1850.6 ?mol FE/g. A very strong positive correlation (r = 0.978) was found between the results of the two assays. While less potent than pure ascorbic acid, the extract's activity is significant for a plant extract. The 70% ethanolic extract of F. benjamina leaves possesses substantial in vitro antioxidant activity, attributed to its high phenolic and flavonoid content. The strong correlation between ABTS and FRAP results indicates complementary antioxidant mechanisms.